Pengembangan Multimedia Pembelajaran Teknik Dasar Hindaran dan Teknik Dasar Tangkapan Berbasis Website Berorientasi Project based learning Pada Mata Kuliah Teori dan Praktik Pembelajaran Pencak Silat: Development of Multimedia Learning of Basic Evasion Techniques and Basic Catching Techniques Based on a Website Oriented to Project Based Learning in the Theory and Practice of Pencak Silat Learning Course - Yogiswara, Oka Ananta; Suwiwa, I Gede; Spyanawati, Ni Luh Putu (Universitas Pendidikan Ganesha, 2025)
This study aims to develop multimedia learning of basic avoidance techniques and basic catch techniques based on project-based learning-oriented websites in the theory and practice of pencak silat learning courses. The type of research used is a type of development research with a development model from Borg & Gall which consists of 1) research and data collection, 2) planning, 3) product draft development, 4) initial field trial, 5) revision of trial results, 6) main product field trial, 7) product revision, 8) wide-scale field trial/feasibility test, 9) final product revision, for the 10th stage, namely dissemination and implementation are not carried out due to time and cost limitations. The subjects in this study were FOK students. The instrument used was a 5 scale with quantitative descriptive data analysis techniques. Based on the results of the study, the learning multimedia design consists of a home menu, learning objectives menu, learning guidelines, learning activities (consisting of determining projects, project planning, preparing implementation schedules, implementing projects with educator guidance), project collection, evaluation, material summary, profile. The validity test of learning multimedia is obtained from the results of the material expert test getting a score of 95%, media expert test 96%, learning design expert test 90%, individual trial 92.5%, small group trial 93.4%, large group trial 96.1%, and practicality test 97.3%. It can be concluded that the design of this learning multimedia consists of a home menu, learning objectives, learning instructions, learning activities, task collection, evaluation, summary and profile. The validity test of learning multimedia obtained very feasible results. The practicality test obtained very practical results. Thus, learning multimedia is declared feasible for use in the pencak silat learning process.